Managing Credit Risk Under The Basel 111 Framework - Lam, Yat-Fai; Kwan, T.; Lai, K. (Amazon, 2014)
This book is developed for teaching a one semester course in credit risk management at undergraduate and MBA levels as the first course in financial risk management. Readers are assumed no prior knowledge in financial risk management. This revolutionary approach aims to broaden the lectures on credit risk management to the majority of students who intend to work in the financial industry. Recognizing that credit risk is the largest risk exposure in financial institutions, this book also seeks to answer the questions that are often raised by practitioners who actually work in the field of credit risk management. Riding on the Basel III framework, the solutions are delivered by contemporary techniques, conforming to the latest regulatory standards. This fills immediately the gap between the working requirements in the office and the academic knowledge in the laboratory. Simply speaking, this book answers specifically the common questions of "how to" in the field of credit risk management.